Perception of Followers Account @modelmuslimahindonesia About Hijabers Contest Photo on Instagram Social Media - Anisa Larasatiningtyas; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2022)
In this study, the purpose of this study was to determine the perception of followers of the @modelmuslimahindonesia account about photo contests on Instagram social media. And the method used in this research is descriptive qualitative. From the results of interviews with followers, which shows that most of them give a positive perception about the hijabers photo contest held on the Instagram account @modelmuslimahindonesia, it has a positive effect or influence, namely being able to develop talent, increase self-confidence starting from the clothes worn, angles or backgrounds that match create perfect results so that they attract Muslim women. As for some of the followers who gave a negative perception of the hijabers photo contest which was held on the Instagram account @modelmuslimahindonsia, starting from the feed not being neat, the criteria for the winner must also be determined and also regarding the costs determined by the Instagram account @modemuslimahindonesia.